PELATIHAN GERAK DASAR DAN PERMAINAN EDUKATIF UNTUK MENINGKATKAN AKTIVITAS FISIK ANAK USIA DINI - Andi Muh. Ruum Sya'baan; Sarnely Uge; Aldiansyah (JESASI (JURNAL EDUKASI, SAINS, DAN INOVASI), 2025)
This study aims to enhance the physical activity and fundamental motor skills of early childhood students through a training program that integrates basic movement exercises with educational games at PAUD “Asmi Abdillah.” The program was implemented using a participatory approach involving 30 children aged 4–6 years over four weeks of structured sessions. Data were collected through observation sheets, pretest and posttest performance assessments, and interviews with teachers. Quantitative analysis using descriptive statistics and a paired sample t-test revealed a significant improvement in children’s motor skills, including running, jumping, and throwing (p < 0.05). The mean score increased from 63.2 in the pretest to 81.3 in the posttest, indicating substantial progress in movement coordination and physical engagement. Qualitative findings from teacher interviews supported these results, highlighting increased enthusiasm, confidence, and social participation among children. Teachers also reported that the activities encouraged creative teaching strategies and improved classroom dynamics. Overall, this training program proved effective in promoting physical literacy, social interaction, and emotional development in early childhood education. The integration of playful, movement-based learning can serve as an innovative model for fostering healthy, active, and confident young learners.